2016
DOI: 10.1109/tro.2016.2570240
|View full text |Cite
|
Sign up to set email alerts
|

Movement Coordination in Human–Robot Teams: A Dynamical Systems Approach

Abstract: Abstract-In order to be effective teammates, robots need to be able to understand high-level human behavior to recognize, anticipate, and adapt to human motion. We have designed a new approach to enable robots to perceive human group motion in real-time, anticipate future actions, and synthesize their own motion accordingly. We explore this within the context of joint action, where humans and robots move together synchronously. In this paper, we present an anticipation method which takes high-level group behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Despite the incredible complexity of such human social interactions, we found that a rather simple mathematical model of coupled Kuramoto oscillators was able to capture most of the features observed experimentally. The availability of a mathematical description of the players' dynamics can be instrumental for designing better architectures driving virtual agents (e.g., robots, computer avatars) to coordinate their motion within groups of humans [53,54,55,56], as well as for predicting the coupling strength needed to restore synchronisation based on initial knowledge of individual consistency, group variance and topology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the incredible complexity of such human social interactions, we found that a rather simple mathematical model of coupled Kuramoto oscillators was able to capture most of the features observed experimentally. The availability of a mathematical description of the players' dynamics can be instrumental for designing better architectures driving virtual agents (e.g., robots, computer avatars) to coordinate their motion within groups of humans [53,54,55,56], as well as for predicting the coupling strength needed to restore synchronisation based on initial knowledge of individual consistency, group variance and topology.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, research groups now shifted to work on realising attention management, turn-taking gaze behaviour and other social gaze behaviour for robots in multi-party interac-tions (e.g., [12][13][14]). Motion in human groups has to be interpreted in real time to anticipate future actions of human group members and synthesize the robots' own motion accordingly [15].…”
Section: Technical Solutions To Handle Multiple Usersmentioning
confidence: 99%
“…Imperfect information complicates the control design problem and may degrade the performance of the overall system. Cooperation with human was adopted to improve the performance of a multi-agent system in complex environments [9][10].To develop practical robot applications, it is necessary to take the environment into consideration, and the more complex the environment is, the more difficult it will be when designing the control law. Complex environments lead to complicated mechanisms, which makes the design problem complex.…”
mentioning
confidence: 99%
“…Imperfect information complicates the control design problem and may degrade the performance of the overall system. Cooperation with human was adopted to improve the performance of a multi-agent system in complex environments [9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation